Wear-resistant, high-strength and environment-friendly antifouling and biological adhesion prevention composite fiber for water body and preparation method of composite fiber
By preparing the composite fibers for water bodies that are wear-resistant, high-strength, environmentally friendly, anti-fouling and biological adhesion, the problem of difficult removal of marine biological adhesion and pollution in traditional cage farming is solved, and efficient anti-fouling and biological adhesion effects are achieved, and the wear resistance and service life of the material are significantly improved.
Patent Information
- Application Number
- CN202411916372.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Traditional cage farming has problems such as pollution caused by marine organisms, reduced dissolved oxygen, poor flow, and difficulty in removing pollution. The existing anti-fouling coatings have problems such as environmental hazards and short anti-fouling effects.
Using a method of preparing composite fibers for water that are wear-resistant, high-strength, environmentally friendly, anti-fouling and biologically adhesion, a modified polyethylene fiber is formed by dispersing fluoro-containing acrylate with benzophenone compounds and thioperoxide dicarbonate in an organic solvent, adding polyethylene resin slices, irradiating under ultraviolet light and passing argon gas to form modified polyethylene fibers, and then coating the meltable perfluoropolymer skin.
The high strength, wear resistance and environmental protection of composite fibers are achieved, while significantly improving the anti-fouling and biological adhesion effects, extending the service life and reducing environmental pollution.
Smart Images

Figure CN119824574A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of materials, and more specifically, to a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies and a preparation method thereof. Background Art
[0002] At present, with the growing demand for seafood, the global cage aquaculture industry is booming. Cage aquaculture is a cage that uses mesh to assemble a certain shape and is placed in a larger body of water. The water inside and outside the cage is exchanged through the mesh, so that a "living water" environment suitable for fish or other aquatic organisms is formed in the cage. This method can make full use of the water space and bait organisms to achieve high-density and high-efficiency aquaculture.
[0003] There are several major problems with traditional cage aquaculture: first, the cages are easily attached by marine organisms such as barnacles and algae, causing the cages to be fouled and forming a fence effect; second, the attachment of marine organisms will also reduce the dissolved oxygen content and food supply in the cages, causing the farmed seafood to develop poorly or even die, seriously affecting the output and quality of seafood farming; third, the poor flow of seawater and increased resistance may cause the cages to be washed away; finally, artificially placed fish feed and fish excrement are difficult to be carried away by flowing seawater, which will cause water pollution in the cages, and then cause fish disease and death.
[0004] At present, although there are various antifouling coatings on the market, they often contain metal ions that are harmful to the environment, and most of them have the problem of short-term antifouling effect. Although these coatings can slow down the attachment of marine organisms to a certain extent, they are not environmentally friendly or sustainable solutions in the long run.
[0005] In view of this, this application is filed. Summary of the invention
[0006] In order to solve the above technical problems, the present application provides a method for preparing a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies.
[0007] This application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water, which comprises: (1) dispersing a fluorinated acrylate, a benzophenone compound, and an alkyl ester containing thioperoxydicarbonate in an organic solvent to obtain a modified liquid, adding polyethylene resin chips to the modified liquid, and stirring under an inert atmosphere to obtain a solid-liquid mixture; (2) irradiating the solid-liquid mixture under 240-260 nm ultraviolet light for 3-48 hours, controlling the temperature of the solid-liquid mixture at 10-60° C. during the irradiation process, continuously stirring and introducing argon gas, and then filtering and drying to obtain fluorinated polyethylene resin chips.
[0008] (3) melt spinning the fluorinated polyethylene resin slices and the polyethylene resin slices according to a mass ratio, and preparing a modified polyethylene fiber having a skin layer of the fluorinated polyethylene resin and a core layer of the unmodified polyethylene resin through heat drawing; (4) Melting and softening the meltable perfluoropolymer at 100-300° C., coating the surface of the modified polyethylene fiber to form a meltable perfluoropolymer skin layer, and then water cooling to obtain a composite fiber, wherein the meltable perfluoropolymer accounts for 5-30% of the total composite fiber mass.
[0009] Furthermore, the meltable perfluoropolymer includes any one of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer and perfluoroethylene propylene copolymer.
[0010] Furthermore, in the modified polyethylene fiber, the fluorine-containing polyethylene resin is the skin layer, and the unmodified polyethylene resin is the core layer, the skin layer accounts for 8-12 parts by weight, and the core layer accounts for 88-92 parts by weight.
[0011] Furthermore, in the above-mentioned modified liquid, the molar ratio of the fluorinated acrylate, the benzophenone compound, and the alkyl ester containing thioperoxydicarbonate is (100-300):1:1.
[0012] Furthermore, the benzophenone compound is a compound represented by Formula 1, and the alkyl ester containing thioperoxydicarbonate is a compound represented by Formula 2:
[0013] Furthermore, in the process of preparing the solid-liquid mixture, the mass ratio of the polyethylene resin slice to the fluorinated acrylate is 1:(0.1-60); the weight average molecular weight of the polyethylene resin slice is 20,000-500,000.
[0014] Furthermore, the above-mentioned fluorine-containing acrylate includes one or a combination of 2-(perfluorobutyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorodecyl)ethyl methacrylate, 2-perfluorooctylethyl acrylate, 3-(perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, and 2-(perfluorododecyl)ethyl acrylate.
[0015] Furthermore, in the above composite melt spinning process, the temperature of the hot drawing is 80-130° C., and the drawing ratio is 3-15 times.
[0016] Furthermore, the tensile strength of the composite fiber for water bodies is ≥6.0 cN / dtex, the amount of biological attachment on the surface after being immersed in seawater for half a year is ≤0.001 g / m, and the amount of biological attachment on the surface after being rubbed 5000 times and immersed in seawater for half a year is ≤0.002 g / m.
[0017] In summary, this application has the following beneficial effects: The composite fiber for water bodies provided in the present application firstly modifies polyethylene resin with fluorinated acrylate to obtain a modified polyethylene fiber with a skin layer of fluorinated polyethylene resin and a core layer of unmodified polyethylene resin, and then coats the surface of the modified polyethylene fiber with a meltable perfluoropolymer to form a composite material. Since fluorinated polymers generally have low surface energy and are not easy to adhere to other substances, after coating with the meltable perfluoropolymer, the composite material has better anti-fouling and anti-biological adhesion effects.
[0018] Compared with the technical solution of directly coating the meltable perfluoropolymer on the unmodified polyethylene resin, due to the low surface energy of the meltable perfluoropolymer, when compounded with the fluorine-free polymer, the two different types of polymers are incompatible, the interface interaction between the two is low, and a good bonding interface cannot be formed, which will greatly affect the performance of the material and cause negative situations such as shedding and delamination. The present application modifies the polyethylene resin and effectively improves the interface bonding force between the meltable perfluoropolymer coating layer and the polyethylene resin material by introducing the modified polyethylene material of fluorine-containing polyethylene, which increases the overall strength of the composite fiber and effectively improves the wear resistance, thereby extending the service life of the fiber and its products and the effective time of preventing biological attachment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the cross-sectional structure of the composite fiber for water bodies provided in this application. DETAILED DESCRIPTION
[0020] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0021] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0022] Example 1 The present embodiment provides a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies, and the preparation method thereof includes: Step 1: using dioxane as a solvent, mixing a benzophenone compound with a structure as shown in Formula 1, a thioperoxydicarbonic acid with a structure as shown in Formula 2, and 2-(perfluorobutyl)ethyl methacrylate in a molar ratio of 1:1:105 to obtain a modified solution. Add polyethylene resin chips with a weight average molecular weight of 100,000 to the modified solution, the mass ratio of the polyethylene resin chips to 2-(perfluorobutyl)ethyl methacrylate is 1:20, and high-purity argon gas is introduced at 200 ml / min, and stirred for 60 minutes to obtain a solid-liquid mixture.
[0023] Step 2: The solid-liquid mixture obtained in step 1 was irradiated with ultraviolet light of wavelength 253 nm for 12 hours. During the irradiation process, the mixture was continuously stirred and argon gas was introduced at an amount of 200 ml / min. The temperature of the solid-liquid mixture was controlled at 20 degrees Celsius. The irradiated solid-liquid mixture was filtered and dried at 60 degrees Celsius for 3 hours to obtain fluorinated polyethylene resin slices.
[0024] Step 3: The fluorinated polyethylene resin slices and polyethylene resin slices obtained in step 2 are used as raw materials and composite melt spinning is performed in a composite spinning machine; the composite spinning machine comprises two single-screw extruders, the spinning temperature of the composite spinning machine is 230 degrees Celsius, the fluorinated polyethylene resin and the unmodified polyethylene resin are respectively added to different single-screw extruders to melt to form a melt, which is metered and transported to the composite spinning component by respectively equipped metering pumps, and extruded through a composite spinneret to obtain a continuous melt with the fluorinated polyethylene as the skin layer and the unmodified polyethylene resin as the core layer, wherein the mass of the fluorinated polyethylene accounts for 8 parts and the mass of the unmodified polyethylene resin accounts for 92 parts; after air cooling and solidification, the modified polyethylene fiber with the skin layer of the fluorinated polyethylene resin and the core layer of the unmodified polyethylene resin is prepared by drawing 8 times at 90 degrees Celsius, wherein the skin layer accounts for 8 parts and the mass of the core layer accounts for 92 parts.
[0025] Step 4: melt and soften the meltable perfluoropolymer PFA resin (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer) at 250 degrees Celsius using a screw extruder, and coat the modified polyethylene fiber surface obtained in step 3 through a 250 degree Celsius melt coating process to form a cortex, and obtain PE / PFA composite fiber after cooling, wherein the mass of the cortex PFA accounts for 13% of the total fiber mass.
[0026] Example 2 The present embodiment provides a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies, and the preparation method thereof includes: Step 1: using dioxane as a solvent, mixing a benzophenone compound with a structure as shown in Formula 1, a thioperoxydicarbonic acid with a structure as shown in Formula 2, and 2-(perfluorooctyl)ethyl methacrylate in a ratio of 1:1:110 to obtain a modified solution. Add polyethylene resin chips with a weight average molecular weight of 80,000 to the modified solution, the mass ratio of the polyethylene resin chips to 2-(perfluorooctyl)ethyl methacrylate is 1:30, and high-purity argon gas is introduced at 200 ml / min, and stirred for 60 minutes to obtain a solid-liquid mixture.
[0027] Step 2: The solid-liquid mixture obtained in step 1 was irradiated with ultraviolet light of wavelength 253 nm for 14 hours. During the irradiation process, the mixture was continuously stirred and argon gas was introduced at an amount of 300 ml / min. The temperature of the solid-liquid mixture was controlled at 25 degrees Celsius. The irradiated solid-liquid mixture was filtered and dried at 60 degrees Celsius for 4 hours to obtain fluorinated polyethylene resin slices.
[0028] Step 3: The fluorinated polyethylene resin slices and polyethylene resin slices obtained in step 2 are used as raw materials and composite melt spinning is performed in a composite spinning machine; the composite spinning machine comprises two single-screw extruders, the spinning temperature of the composite spinning machine is 230 degrees Celsius, the fluorinated polyethylene resin and the unmodified polyethylene resin are respectively added to different single-screw extruders to melt to form a melt, which is metered and transported to the composite spinning component by respectively equipped metering pumps, and extruded through a composite spinneret to obtain a continuous melt with the fluorinated polyethylene as the skin layer and the unmodified polyethylene resin as the core layer, wherein the mass of the fluorinated polyethylene accounts for 9 parts and the mass of the unmodified polyethylene resin accounts for 91 parts; after air cooling and solidification, the modified polyethylene fiber with the skin layer of the fluorinated polyethylene resin and the core layer of the unmodified polyethylene resin is prepared by drawing 10 times at 110 degrees Celsius, wherein the skin layer accounts for 9 parts and the mass of the core layer accounts for 91 parts.
[0029] Step 4: melt and soften the meltable perfluoropolymer PFA resin at 255 degrees Celsius using a screw extruder, and coat the modified polyethylene fiber surface obtained in step 3 with a 255 degree Celsius melt coating process to form a cortex, and obtain a PE / PFA composite fiber after cooling, wherein the mass of the cortex PFA accounts for 12% of the total fiber mass.
[0030] Example 3 The present embodiment provides a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies, and the preparation method thereof includes: Step 1: using dioxane as a solvent, mixing a benzophenone compound with a structure as shown in Formula 1, a thioperoxydicarbonic acid with a structure as shown in Formula 2, and 2-(perfluorohexyl)ethyl methacrylate in a ratio of 1:1:120 to obtain a modified solution. Add polyethylene resin chips with a weight average molecular weight of 100,000 to the modified solution, the mass ratio of the polyethylene resin chips to 2-(perfluorohexyl)ethyl methacrylate is 1:50, and high-purity argon gas is introduced at 200 ml / min, and stirred for 60 minutes to obtain a solid-liquid mixture.
[0031] Step 2: The solid-liquid mixture obtained in step 1 was irradiated with ultraviolet light of wavelength 253 nm for 15 hours. During the irradiation process, the mixture was continuously stirred and argon gas was introduced at an amount of 320 ml / min. The temperature of the solid-liquid mixture was controlled at 30 degrees Celsius. The irradiated solid-liquid mixture was filtered and dried at 65 degrees Celsius for 4 hours to obtain fluorinated polyethylene resin slices.
[0032] Step 3: The fluorinated polyethylene resin slices and polyethylene resin slices obtained in step 2 are used as raw materials and composite melt spinning is performed in a composite spinning machine; the composite spinning machine comprises two single-screw extruders, the spinning temperature of the composite spinning machine is 230 degrees Celsius, the fluorinated polyethylene resin and the unmodified polyethylene resin are respectively added to different single-screw extruders to melt to form a melt, which is metered and transported to the composite spinning component by respectively equipped metering pumps, and extruded through a composite spinneret to obtain a continuous melt with the fluorinated polyethylene as the skin layer and the unmodified polyethylene resin as the core layer, wherein the mass of the fluorinated polyethylene accounts for 10 parts and the mass of the unmodified polyethylene resin accounts for 90 parts; after air cooling and solidification, the modified polyethylene fiber with the skin layer of the fluorinated polyethylene resin and the core layer of the unmodified polyethylene resin is prepared by drawing 10 times at 113 degrees Celsius, wherein the skin layer accounts for 10 parts and the mass of the core layer accounts for 90 parts.
[0033] Step 4: melt and soften the meltable perfluoropolymer FEP resin (perfluoroethylene propylene copolymer) at 256 degrees Celsius using a screw extruder, and coat the modified polyethylene fiber surface obtained in step 3 through a 256 degree Celsius melt coating process to form a cortex, and obtain a PE / FEP composite fiber after cooling, wherein the mass of the cortex FEP accounts for 12% of the total fiber mass.
[0034] Example 4 The present embodiment provides a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies, and the preparation method thereof includes: Step 1: using dioxane as a solvent, mixing a benzophenone compound with a structure as shown in Formula 1, a thioperoxydicarbonic acid with a structure as shown in Formula 2, and 2-(perfluorodecyl)ethyl methacrylate at a ratio of 1:1:140 to obtain a modified solution. Add polyethylene resin chips with a weight average molecular weight of 150,000 to the modified solution, the mass ratio of the polyethylene resin chips to 2-(perfluorodecyl)ethyl methacrylate is 1:60, and high-purity argon gas is introduced at 200 ml / min, and stirred for 60 minutes to obtain a solid-liquid mixture.
[0035] Step 2: The solid-liquid mixture obtained in step 1 was irradiated with ultraviolet light of wavelength 253 nm for 20 hours. During the irradiation process, the mixture was continuously stirred and argon gas was introduced at a rate of 450 ml / min. The temperature of the solid-liquid mixture was controlled at 40 degrees Celsius. The irradiated solid-liquid mixture was filtered and dried at 70 degrees Celsius for 5 hours to obtain fluorinated polyethylene resin slices.
[0036] Step 3: The fluorinated polyethylene resin slices and polyethylene resin slices obtained in step 2 are used as raw materials and composite melt spinning is performed in a composite spinning machine; the composite spinning machine comprises two single-screw extruders, and the spinning temperature is 230 degrees Celsius. The fluorinated polyethylene resin and the unmodified polyethylene resin are respectively added to different single-screw extruders for melting to form a melt, which is metered and transported to the composite spinning assembly by respectively equipped metering pumps, and extruded through a composite spinneret to obtain a continuous melt with the fluorinated polyethylene as the skin layer and the unmodified polyethylene resin as the core layer, in which the mass of the fluorinated polyethylene accounts for 12 parts and the mass of the unmodified polyethylene resin accounts for 88 parts; the modified polyethylene fiber with the skin layer of the fluorinated polyethylene resin and the core layer of the unmodified polyethylene resin is prepared by air cooling and solidification, and is stretched 12 times at 125 degrees Celsius to obtain a modified polyethylene fiber with the skin layer of the fluorinated polyethylene resin and the core layer of the unmodified polyethylene resin, in which the mass of the skin layer accounts for 12 parts and the mass of the core layer accounts for 88 parts.
[0037] Step 4: melt and soften the meltable perfluoropolymer FEP resin at 260 degrees Celsius using a screw extruder, and coat the modified polyethylene fiber surface obtained in step 3 through a 260 degree Celsius melt coating process to form a skin layer, and obtain a PE / FEP composite fiber after cooling, wherein the mass of the skin layer FEP accounts for 10% of the total fiber mass.
[0038] Example 5 The difference between this embodiment and embodiment 1 is that: Step 1: 1,1,1,3,3,3-hexafluoroisopropyl acrylate is used as the fluorine-containing acrylate, and the molar ratio of the benzophenone compound shown in Formula 1, the thioperoxydicarbonic acid compound shown in Formula 2, and the fluorine-containing acrylate is 1:1:300.
[0039] Example 6 The difference between this embodiment and embodiment 1 is that: Step 1: 2-(perfluorododecyl)ethyl acrylate is used as the fluorinated acrylate, and the molar ratio of the benzophenone compound shown in Formula 1, the thioperoxydicarbonic acid compound shown in Formula 2, and the fluorinated acrylate is 1:1:100.
[0040] Example 7 The difference between this embodiment and embodiment 1 is that: Step 2: The solid-liquid mixture obtained in step 1 is irradiated with ultraviolet light of wavelength 240 nm for 48 hours. During the irradiation process, the mixture is continuously stirred and argon is introduced at a rate of 450 ml / min. The temperature of the solid-liquid mixture is controlled at 50-60 degrees Celsius. The irradiated solid-liquid mixture is filtered and dried at 70 degrees Celsius for 5 hours to obtain fluorinated polyethylene resin slices.
[0041] Example 8 The difference between this embodiment and embodiment 1 is that: Step 2: The solid-liquid mixture obtained in step 1 is irradiated with ultraviolet light of wavelength 260 nm for 3 hours. During the irradiation process, the mixture is continuously stirred and argon is introduced at a rate of 450 ml / min. The temperature of the solid-liquid mixture is controlled at 10-30 degrees Celsius. The irradiated solid-liquid mixture is filtered and dried at 70 degrees Celsius for 5 hours to obtain fluorinated polyethylene resin slices.
[0042] Example 9 The difference between this embodiment and embodiment 1 is that: Step 3: The fluorinated polyethylene resin and the unmodified polyethylene resin are added to different single-screw extruders to melt and form a melt, which is solidified after air cooling and stretched 3 times at 80 degrees Celsius to obtain a modified polyethylene fiber with a skin layer of fluorinated polyethylene resin and a core layer of unmodified polyethylene resin, wherein the skin layer accounts for 8 parts by weight and the core layer accounts for 92 parts by weight.
[0043] Example 10 The difference between this embodiment and embodiment 1 is that: Step 3: The fluorinated polyethylene resin and the unmodified polyethylene resin are added to different single-screw extruders to melt and form a melt, which is solidified after air cooling and stretched 15 times at 130 degrees Celsius to prepare a modified polyethylene fiber with a skin layer of fluorinated polyethylene resin and a core layer of unmodified polyethylene resin, with the skin layer accounting for 8 parts by weight and the core layer accounting for 92 parts by weight.
[0044] Example 12 The difference between this embodiment and embodiment 1 is that: Step 4: melt and soften the meltable perfluoropolymer PFA resin (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer) at 100 degrees Celsius using a screw extruder, and coat the modified polyethylene fiber surface obtained in step 3 through a 100 degrees Celsius melt coating process to form a cortex, and obtain a PE / PFA composite fiber after cooling, wherein the mass of the cortex PFA accounts for 5% of the total fiber mass.
[0045] Example 13 The difference between this embodiment and embodiment 1 is that: Step 4: melt and soften the meltable perfluoropolymer FEP resin (perfluoroethylene propylene copolymer) at 300 degrees Celsius using a screw extruder, and coat the modified polyethylene fiber surface obtained in step 3 through a 300 degree Celsius melt coating process to form a cortex, and obtain a PE / FEP composite fiber after cooling, wherein the mass of the cortex FEP accounts for 30% of the total fiber mass.
[0046] Comparative Example Comparative Example 1 The preparation method of this comparative example is as follows: Step 1: Spin polyethylene chips with a weight average molecular weight of 100,000 at 230 degrees Celsius, and draw them 8 times at 90 degrees Celsius to obtain polyethylene fibers.
[0047] Step 2: melt and soften the meltable perfluoropolymer PFA resin at 250 degrees Celsius using a screw extruder, and coat the polyethylene fiber surface obtained in step 1 through a 250 degree Celsius melt coating process to form a cortex, and obtain a PE / PFA composite fiber after cooling, wherein the mass of the cortex PFA accounts for 13% of the total mass.
[0048] Comparative Example 2 The preparation method of this comparative example is as follows: Step 1: Spin polyethylene chips with a weight average molecular weight of 80,000 at 220 degrees Celsius, and draw them 10 times at 110 degrees Celsius to obtain polyethylene fibers.
[0049] Step 2: melt and soften the meltable perfluoropolymer FEP resin at 255 degrees Celsius using a screw extruder, and coat the polyethylene fiber surface obtained in step 1 through a 255 degree Celsius melt coating process to form a skin layer, and obtain a PE / FEP composite fiber after cooling, wherein the mass of the skin layer FEP accounts for 12% of the total mass.
[0050] Comparative Example 3 The preparation method of this comparative example is as follows: Polyethylene chips with a weight average molecular weight of 100,000 were spun at 230 degrees Celsius and stretched 8 times at 90 degrees Celsius to obtain polyethylene fibers.
[0051] Comparative Example 4 The preparation method of this comparative example is as follows: Polyethylene chips with a weight average molecular weight of 80,000 were spun at 220 degrees Celsius and stretched 10 times at 110 degrees Celsius to obtain polyethylene fibers.
[0052] Comparative Example 5 The difference between this comparative example and Example 1 is that the PFA resin is replaced with an equal amount of polyvinylidene fluoride (PVDF).
[0053] Comparative Example 6 The difference between this comparative example and Example 1 is that the polyethylene resin chips with a weight average molecular weight of 100,000 are replaced by an equal amount of polypropylene (PP) with a weight average molecular weight of 100,000.
[0054] Comparative Example 7 The difference between this comparative example and Example 1 is that the polyethylene resin chips with a weight average molecular weight of 100,000 are replaced by an equal amount of polyamide (PA) with a weight average molecular weight of 100,000.
[0055] Performance testing The tensile properties of the composite fibers provided in the above embodiments and comparative examples were frequently tested using GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments". The amount of biological attachment on the surface of the composite fibers after immersion in seawater for half a year was calculated using the weighing method. The composite fibers were rubbed on 500-mesh sandpaper to evaluate the wear resistance. The test results are shown in Table 1: Table 1 Fiber properties of various embodiments and comparative examples It can be seen from the above table that the PE / PFA composite fiber and PE / FEP composite fiber prepared in the present application have excellent tensile strength, and the wear resistance is significantly improved compared with the products obtained by the conventional method, especially the wear resistance index is significantly improved, which shows that the method of the present invention can effectively improve the performance of the fiber.
[0056] In terms of the amount of biological adhesion on the surface after being immersed in seawater for half a year, Examples 1 to 4, Comparative Examples 1 and 2 coated with a meltable perfluoropolymer (PFA or FEP) skin layer all exhibited better anti-adhesion properties than Comparative Examples 3 and 4, which is mainly due to the low surface energy of the PFA material. At the same time, the amount of biological adhesion on the surface of the fiber coated with PVDF (Comparative Example 5) was also less than that of Examples 1 and 2, indicating that the low surface energy of PFA and FEP materials is better than that of PVDF.
[0057] After simulating the friction environment in daily use, since the fibers of Examples 1 to 4 of the present invention adopt a new and improved process, the wear resistance can be effectively improved, and the fusible perfluoropolymer coating layer of the fiber is retained, so the amount of biological attachment on the fiber surface is still very low, reflecting excellent and lasting anti-biological attachment; while in Comparative Examples 1 and 2, due to the low interaction force between the core layer polyethylene and the fusible perfluoropolymer of the skin layer, they are easily separated under the friction in daily use, and the fiber surface will be damaged and roughened, causing the fusible perfluoropolymer layer to fall off, thereby greatly affecting the original anti-biological attachment effect. This is the reason why the amount of biological attachment on the fiber surface of Comparative Examples 1 and 2 in the table is significantly increased after friction. At the same time, compared with Example 1, Comparative Examples 7 and 8, due to the different core layer materials used, although they have also undergone the same modification treatment, their wear resistance and mechanical properties under the same conditions are very weak.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies, characterized in that: It includes: Dispersing fluorinated acrylate, benzophenone compounds, and alkyl esters containing thioperoxydicarbonate in an organic solvent to obtain a modified liquid, adding polyethylene resin chips to the modified liquid, and stirring under an inert atmosphere to obtain a solid-liquid mixture; The solid-liquid mixture is irradiated under ultraviolet light of 240-260 nm for 3-48 hours, during which the temperature of the solid-liquid mixture is controlled at 10-60° C., the mixture is continuously stirred and argon is introduced, and then filtered and dried to obtain fluorine-containing polyethylene resin slices; the fluorine-containing polyethylene resin slices and polyethylene resin slices are composite melt-spun according to a mass ratio, and modified polyethylene fibers having a skin layer of fluorine-containing polyethylene resin and a core layer of unmodified polyethylene resin are prepared by heat drawing; The meltable perfluoropolymer is melted and softened at 100-300°C, coated on the surface of the modified polyethylene fiber to form a meltable perfluoropolymer skin layer, and then water-cooled to obtain a composite fiber, wherein the meltable perfluoropolymer accounts for 5-30% of the total composite fiber mass.
2. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: The meltable perfluoropolymer includes any one of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer and perfluoroethylene propylene copolymer.
3. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: In the modified polyethylene fiber, the fluorine-containing polyethylene resin is the skin layer, and the unmodified polyethylene resin is the core layer. The weight of the skin layer accounts for 8-12 parts, and the weight of the core layer accounts for 88-92 parts.
4. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: In the modified liquid, the molar ratio of the fluorine-containing acrylate, the benzophenone compound, and the alkyl ester containing thioperoxydicarbonate is (100-300):1:
1.
5. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: The benzophenone compound is a compound shown in Formula 1, and the alkyl ester containing thioperoxydicarbonate is a compound shown in Formula 2:
6. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: In the process of preparing the solid-liquid mixture, the mass ratio of the polyethylene resin slice to the fluorine-containing acrylate is 1:(0.1-60); the weight average molecular weight of the polyethylene resin slice is 20,000-500,000.
7. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: The fluorine-containing acrylate includes one or a combination of 2-(perfluorobutyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorodecyl)ethyl methacrylate, 2-perfluorooctylethyl acrylate, 3-(perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, and 2-(perfluorododecyl)ethyl acrylate.
8. The method for preparing the wear-resistant, high-strength, environmentally friendly, anti-fouling and anti-biological attachment composite fiber for water bodies according to claim 1, characterized in that: In the composite melt spinning process, the temperature of the hot drawing is 80-130° C., and the drawing multiple is 3-15 times.
9. A composite fiber for water obtained by the preparation method according to any one of claims 1 to 8.
10. The composite fiber for water use according to claim 9, characterized in that: The tensile strength of the composite fiber for water bodies is ≥6.0 cN / dtex, the amount of biological attachment on the surface after being immersed in seawater for half a year is ≤0.001 g / m, and the amount of biological attachment on the surface after being immersed in seawater for half a year after being rubbed 5000 times is ≤0.002 g / m.
Citation Information
Patent Citations
Fluorescent non-woven fabric for sanitary products and manufacturing method of fluorescent non-woven fabric
CN110387640A
Somatosensory cool fiber fabric with waterproof, oil-proof and antifouling functions
CN110522106A
Fiber having effects of safety and preventing aquatic life adhesion
JP1996134779A
Sheath-core conjugate fiber containing fluorine-containing polymer in sheath and article having the conjugate fiber
JP2007211376A